Proceedings of the 4th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle 2007
DOI: 10.17077/drivingassessment.1289
|View full text |Cite
|
Sign up to set email alerts
|

Risky Driving by Recently Licensed Teens: Self-Reports and Simulated Performance

Abstract: Summary: U.S. teens are overrepresented in motor vehicle crashes, with the majority due to driver error; however, causal pathways remain to be elucidated. This research aimed to identify driving performance factors that might underlie newly-licensed male teens' risk. Surveys were conducted with 21 16-year-olds at the time of intermediate licensure. During the second month of licensure they completed drives in a high-fidelity simulator. Simulator scenarios allowed assessment of responses to yellow traffic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The purpose of this current study is to examine the likelihood that a driver will proceed through an intersection when a light turns yellow. A similar analysis was conducted on this data by Senserrick et al (2007) and findings already showed that novice drivers (age 16 years) ran more yellow lights when compared to other age groups. This current study extends upon Senserrick et al (2007)'s work by also considering the interactions with driver distraction factors and time to stop line (TSL).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…The purpose of this current study is to examine the likelihood that a driver will proceed through an intersection when a light turns yellow. A similar analysis was conducted on this data by Senserrick et al (2007) and findings already showed that novice drivers (age 16 years) ran more yellow lights when compared to other age groups. This current study extends upon Senserrick et al (2007)'s work by also considering the interactions with driver distraction factors and time to stop line (TSL).…”
Section: Introductionmentioning
confidence: 57%
“…A similar analysis was conducted on this data by Senserrick et al (2007) and findings already showed that novice drivers (age 16 years) ran more yellow lights when compared to other age groups. This current study extends upon Senserrick et al (2007)'s work by also considering the interactions with driver distraction factors and time to stop line (TSL). The length of yellow light phase timing, which is closely related to time to stop line, has been shown to predict red-light compliance (Retting & Greene, 1997).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…The error-score had a more erratic pattern as a function of age and is therefore not shown. 4.6% of the men and 14.6% of the women had an error-score greater than 1. have also been used recently to study aggressive driving and road rage , running yellow/red lights (Allen et al, 2005b;Senserrick et al, 2007), voluntary violations (Chalmé et al, 2006), and violating behaviour under time pressure (Bonsall & Palmer, 1997). An interesting finding of Chalmé et al (2006) was that there were large individual differences: There were participants who (almost) never voluntarily violated a rule and others who made a large number of violations.…”
Section: Quantifying Violationsmentioning
confidence: 99%
“…Previous driving simulator studies have shown that age of driver (Senserrick et al, 2007) and the time to stop line (Caird et al, 2007) had significant impact on drivers' decision to stop or not at a yellow signal indication. Hurwitz et al (2012) applied fuzzy logic modeling distance to stop line and vehicle position to predict drivers stopping probability.…”
Section: Introductionmentioning
confidence: 99%